GAMBARAN OTITIS MEDIA SUPURATIF KRONIS BERDASARKAN GAMBARAN RADIOLOGI MASTOID DI RUMAH SAKIT UMUM DAERAH MEURAXA KOTA BANDA ACEH - Fuziati Fuziati; Isfanda Isfanda; Maidayani Maidayani (Jurnal Sains Riset, 2021)
The prevalence of chronic suppurative otitis media in some countries is partly due to social, economic, densely populated, hygienic and poor nutrition conditions. Chronic otitis media is the most common ENT disease in developing countries. The purpose of this research is to know the description of chronic suppurative otitis media (OMSK) based on mastoid radiology picture at Meuraxa General Hospital of Banda Aceh City Year 2017. This research is descriptive conducted on May 18 - July 10, 2017. Respondent is 25 respondents conducted by taking data from medical records. In general, the results showed that the picture of chronic suppurative otitis media (OMSK) based on mastoid radiology picture at Meuraxa Municipal General Hospital of Banda Aceh City in 2017, was in negative mastoiditis category, 21 respondents (84.0%). Based on the above results it is expected to patients to always control the condition of the ear in order to prevent the occurrence of mastoiditis in the ear that can interfere with the auditory system.Keywords: Chronic Suppurative Otitis Media (OMSK), Mastoiditis